Akibat Hukum Kepailitan terhadap Kewenangan Notaris dalam Pembuatan Akta Otentik - Andi Nisa Hayatu Dinia; Fitria Yuseva; Iloni Chiaratumanda; Nadila Debby Ramadhania; Shafrida Shafrida (Jurnal Hukum Lex Generalis, 2026)
Bankruptcy creates legal consequences for the status and authority of legal subjects, including notaries as public officials. This study aims to analyze the legal consequences of bankruptcy on notarial authority in the making of authentic deeds under prevailing laws and regulations. This research employs a normative legal method with statutory and conceptual approaches. The results indicate that bankruptcy does not automatically revoke the position of a notary, but limits authority related to the management and control of assets. Therefore, legal certainty of authentic deeds must be maintained as long as the notary complies with applicable legal provisions.